Tinjauan Desain terhadap Transformasi Visual Karakter Pikachu dalam Game PokÃ©mon Series sebagai Budaya Populer - Aryani, Dewi Isma (Zenit, 2014)
Game Pokémon is a RPG game which has advantages in terms of postmodern culture meanings and symbols available in each element of the characters; morever, the gameplay is built ininside the Pokémon game series. These postmodern culture meanings stem from childhood experiences, traditions and simplification of information and knowledge about the nature of the phenomenon that becomes the initial concept of designing Pokémon game characters. The effort of Pokémon game and animation is to lift up and introduce the culture and characteristics of a system of social values in Japan: the culture of respect for parents or elders, the culture of shame and apology at every mistake, cultural groups, cultural hierarchy of seniority (nenkoujoretsu), optimism, selfreliance, obligation to bear any responsibilities, and so on, are not obviously or semiotically displayed.Keywords: meanings, symbols, game, characters, semiotic, popular culture